In situ IR spectroscopic studies of the avidin-biotin bioconjugation reaction on CdS particle films - Young, Aidan G (Langmuir : the ACS journal of surfaces and colloids, 2009)
Avidin-biotin bioconjugation reactions have been carried out on CdS nanoparticle films in H2O and D2O and investigated using in situ ATR-IR spectroscopic techniques. The experimental procedure involved the sequential adsorption of mercaptoacetic acid, the protein avidin, and the subsequent binding of the ligand biotin. The IR spectra of the solution-phase species mercaptoacetic acid, avidin, and biotin, at pH=7.2 were generally found to be similar in both H2O and D2O, with some minor peak shifts due to solvation changes. The IR spectra of the adsorbed species suggested that avidin may have undergone a conformational change upon adsorption to the CdS surface. In general, adsorption-induced conformational changes for avidin are likely, but to our knowledge have not been previously reported. The conformation of adsorbed avidin appeared to change again upon the binding of biotin, with the spectral data suggesting partial reversion to its native solution conformation